Comparative Analysis of Energy Vectors for Industrial Applications: Evaluating Electricity, Hydrogen, and Biodiesel in the Italian Aluminum Smelting Sector - Finocchi, Emiliano (Current Approaches in Engineering Research and Technology Vol. 8, 2024)
This chapter explores the comparative viability of electricity, hydrogen, and biodiesel as energy vectors for industrial applications, specifically focusing on an aluminum smelter project in Southern Italy. The analysis evaluates each energy vector across multiple parameters, including system efficiency, land requirements for carbon-neutral energy production, and capital expenditure (CapEx). The study finds that while biodiesel offers carbon neutrality, it is impractical due to extensive land requirements and lower efficiency. Hydrogen, though a promising alternative, presents challenges in efficiency and higher CapEx, particularly when considering the infrastructure required for production and transportation. Electricity emerges as the most viable option, offering superior efficiency, lower land requirements, and comparatively lower CapEx. The findings underscore the importance of a holistic assessment of energy vectors in industrial contexts, balancing economic, environmental, and practical considerations to achieve long-term sustainability and feasibility. This comprehensive analysis provides valuable insights and guidance for similar industrial applications, highlighting electricity's potential as the main vector for achieving carbon neutrality in energy-intensive sectors. The implications drawn underscore the need for holistic approaches to policymaking, research, and practice in navigating the transition toward sustainable energy solutions. Further research that addresses these limitations can pave the way for more informed, effective, and sustainable energy strategies in the industrial sector and beyond.